2021
DOI: 10.1002/jrs.6262
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the sensitivity of surface‐enhanced Raman scattering detection for s‐triazine pesticides by taking advantage of interactions with soil humic substances

Abstract: Surface-enhanced Raman scattering (SERS) is a technique which has been well explored for detecting contaminating substances, such as pesticides. Of particular interest has been the use of SERS for quantifying trace levels of the striazine compounds, unraveling the adsorption mechanisms on metallic nanoparticles. Herein, we applied silver nanoparticles (AgNP) as SERS substrates for detecting commercial samples of the pesticides prometryn (PRM) and atrazine (ATZ) and their purified samples in the presence of soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…At this linear regime, no intermolecular interactions are predicted to occur and a calibration curve was used to determine the limit of detection (LOD) of the SERRS immunoassay platform [ 76 , 78 ]. LOD was calculated according to the following equation [ 48 , 77 , 79 , 80 ]: where SD Blank is the standard deviation of the “Blank” sample and b is the slope of the calibration curve. The LOD (0.046 ng/mL or 0.60 pM) obtained here is compared in Table 2 with published research results of detection of SARS-CoV-2 spike (S1) glycoprotein.…”
Section: Resultsmentioning
confidence: 99%
“…At this linear regime, no intermolecular interactions are predicted to occur and a calibration curve was used to determine the limit of detection (LOD) of the SERRS immunoassay platform [ 76 , 78 ]. LOD was calculated according to the following equation [ 48 , 77 , 79 , 80 ]: where SD Blank is the standard deviation of the “Blank” sample and b is the slope of the calibration curve. The LOD (0.046 ng/mL or 0.60 pM) obtained here is compared in Table 2 with published research results of detection of SARS-CoV-2 spike (S1) glycoprotein.…”
Section: Resultsmentioning
confidence: 99%
“…They also used AuNPs as the SERS substrate to detect deltamethrin and carbofuran in soil [ 26 ]. With regard to AgNPs, Sanchez-Cortes et al found that prometryn and atrazine in the soil can be detected by using AgNPs as SERS substrates ( Figure 3 a) [ 27 ]. Additionally, this method can be used to analyze DEHA quantitatively [ 28 ].…”
Section: The Role Of Nanoparticles In the Detection Of Pesticidesmentioning
confidence: 99%
“… Detection of pesticides based on the SERS of nanoparticles ( a ) Soil humic substances-assisted AgNPs SERS substrates for the detection of s-triazine pesticides [ 27 ]. ( b ) Preparation of Ag-nanoplate decorated graphene-sheet SERS substrates for the detection of organic pesticides [ 29 ].…”
Section: The Role Of Nanoparticles In the Detection Of Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…(123)(124)(125) Um dos efeitos utilizados é o efeito Raman com amplificação de superfície (SERS, do inglês Surface-Enhanced Raman Scattering ) (126), usado neste capítulo para diagnóstico de COVID-19. A espectroscopia SERS tem sido utilizada como uma técnica altamente sensível para detectar várias classes de compostos de interesse, incluindo proteínas (biomarcadores de câncer e antígenos virais) (127,128), poluentes emergentes (129), metais pesados (130) e neurotransmissores. (131) O biossensor plasmônico foi constituído de nanopartículas de ouro sobre as quais foram imobilizados anticorpos correspondentes à proteína S do vírus SARS-CoV-2.…”
Section: Introductionunclassified